التزامات مقدمي الخدمة عبر الانترنت - بعجي, محمد (Université de M'sila, 2019)
تتمّ الخدمات المقدمة عبر الانترنت من خلال أشخاص يسمّون بمقدمي الخدمات و هم: متعهد الوصول، و مورد الخدمة أو المعلومة، و ناقل المعلومة، و موردو خدمات البحث. و لمقدمي خدمة الدخول إلى الانترنت التزامات منها، الالتزامات الخاصة و تتمثّل في سحب المحتوى غير المشروع، و التزامهم أيضا بوضع الترتيبات التقنية لحصر إمكانية الدخول للمعلومات غير المشروعة، كما يقع عليهم أيضا في مجال الإعلام و الاتصال وفقا للقانون رقم 09/04 التزامات منها ، الالتزام بمساعدة سلطات الضبط القضائي و الالتزام بحفظ المعطيات المتعلّقة بحركة السير. Abstract: Online services are provided by persons called service providers, tke operator, the service provider or the information, the information carrier, and the providers of research services. Internet access providers have obligations, including obligations, to withdraw illegal content, and also to make technical arrangements for restricting access to illegal information, as well as in the field of information and communication in accordance with law no° 09/04obligation the obligation to assist the judicial control authorities and the obligation to preserve passage data
Keywords: الانترنت ; الخدمات ; الالتزامات ; مقدمي الخدمات ; the Internet ; the services ; the obligations ; services providers